Analisis Stilistika Pada Puisi “Perempuan Yang Tergusur” Karya W.S Rendra - Siti Nurullika Gustira (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research aims to determine the use of language styles, describe the diction and message to be conveyed in the poem